Idea of University, Neoliberalism, and Feminist Movement. Reflections From a Gender Perspective - Garrido-Rivera, Andrea Cecilia; Soto-Muñoz, María Eugenia; Aparicio-Molina, Carolina; Correa-Pérez, Roxanna (Revista Electrónica Educare, 2025)
Introduction. The essay deals with the history of the institution of higher education as a conceptual category, focusing on the concept of the university and the models that have prevailed since its inception as referents that allow it to be structurally characterized and that need to be reviewed from a gender perspective. Aim. The aim of this reflection is to make a critical analysis of the idea of the androcentric university, with the intention of promoting the configuration of new conceptual categories for institutionalism. Discussion. The imaginaries of the idea of the university that emerge from the conceptual review reveal the presence of an androcentric vision in its genesis, anchored in an apparent neutrality that is maintained today with the imprint of later neoliberalism. This is expressed in an academy subject to accountability, with a refinement of academic segregation, where the gendered division of labor is still present, as well as the emergence of other manifestations of inequality. As a turning point, it is worth noting how social movements, and especially feminist movements, allow for a small hopeful reversal of the installed condition. Conclusion. The reflection carried out in this essay, on the one hand, presents some concepts that can contribute to the redefinition of new frames of reference to characterize the university institution from a gender perspective and, on the other hand, projects the revision of important categories not addressed in this exercise, such as decoloniality, intersectionalities, imbrication, and the queer movement, coming from empirical university contexts at the national or international level.